2008
DOI: 10.1371/journal.pone.0002600
|View full text |Cite
|
Sign up to set email alerts
|

Binding to the Minor Groove of the Double-Strand, Tau Protein Prevents DNA from Damage by Peroxidation

Abstract: Tau, an important microtubule associated protein, has been found to bind to DNA, and to be localized in the nuclei of both neurons and some non-neuronal cells. Here, using electrophoretic mobility shifting assay (EMSA) in the presence of DNA with different chain-lengths, we observed that tau protein favored binding to a 13 bp or a longer polynucleotide. The results from atomic force microscopy also showed that tau protein preferred a 13 bp polynucleotide to a 12 bp or shorter polynucleotide. In a competitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 46 publications
5
103
1
1
Order By: Relevance
“…The new interest extends to the nucleus where tau is believed to have an important scaffolding function [13,27]. Because, in the past, data on nuclear tau expression have been inconsistent, in part because of different fixation methods and experimental systems, we validated three principal methods: immunocytochemical staining of human and murine neuroblastoma cell lines testing six protocols, subcellular fractionation of wild-type and human tau transgenic mouse brain, and isolation of nuclei from mouse brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new interest extends to the nucleus where tau is believed to have an important scaffolding function [13,27]. Because, in the past, data on nuclear tau expression have been inconsistent, in part because of different fixation methods and experimental systems, we validated three principal methods: immunocytochemical staining of human and murine neuroblastoma cell lines testing six protocols, subcellular fractionation of wild-type and human tau transgenic mouse brain, and isolation of nuclei from mouse brain.…”
Section: Discussionmentioning
confidence: 99%
“…The punctate pattern seen for Tau-1 in our immunocytochemical study in SH-SY5Y cells is reminiscent of that of nucleoli although this has not been further investigated. In vitro studies further revealed that purified tau binds to AT-rich sequences in the minor groove of DNA [27]. Using an electrophoretic mobility shift assay (EMSA) it was shown that both the proline-rich domain and the microtubule-binding domain contribute to the interaction of tau with DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that nuclear Tau binds preferentially to polynucleotides of 13 bp in length, while further research has indicated that Tau binds to the minor groove of the DNA double helix and that both its proline-rich domain (PRD) and microtubulebinding domain (MTBD) contribute to its interaction with DNA. This binding protects DNA from both digestion by DNase I and damage by peroxidation (Wei et al, 2008).…”
Section: Formaldehyde-induced Aggregation Interferes With Tau's Protementioning
confidence: 99%
“…Tau has been reported to bind single-and double-stranded DNA via the minor groove (26,27,84,85), thereby drawing parallels between Tau and histones in terms of DNA binding. Indeed, monomers or small oligomers of Tau can bind to DNA complexes and give rise to a "beads-on-a-string" organization like histone-DNA assembly (80,84), thus suggesting that Tau could act like a chaperone (26,27,84). Although larger aggregates of Tau interact only weakly with DNA (84,86), complexes between large Tau aggregates and DNA have been observed in vitro, suggesting that different Tau-DNA structures exist (84).…”
Section: Aicd A␤42 and Tau Interactions With Dnamentioning
confidence: 99%
“…In vitro, Wei et al (80) showed that Tau-DNA binding protected DNA from damage induced by free hydroxyl radicals, likely through its capacity to bind to the AT-rich minor groove of DNA (i.e. a common way for proteins to physically protect DNA from damage by inducing its bending).…”
Section: Possible Nuclear Functions Of Aicd A␤ and Taumentioning
confidence: 99%